2003
DOI: 10.1089/107555303322284794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginseng Saponins on the Recombinant Serotonin Type 3A Receptor Expressed in Xenopus Oocytes: Implication of Possible Application as an Antiemetic

Abstract: These results indicate that ginseng saponins, especially PT fraction, have substantial inhibitory effects on the recombinant 5HT(3A) receptor, suggesting that some of the specific types of ginsenoside might have an antagonistic action against 5HT(3A) receptor related to nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
2
6
0
1
Order By: Relevance
“…Ginsenosides (Rg 1 , Re or Rg 2 ) have been acknowledged as key regulators of the 5HT3A receptor during emesis. Another study reports that Rb 1 and Rg 1 exert a similar degree of inhibitory activity on the 5HT3A receptor in Xenopus laevis oocytes Min et al, 2003). The HPLC analysis of RG in this study revealed relatively high and moderate concentrations of the protopanaxadiol ginsenosides Rb 1 , Rg 3, Rc, Rb 2 , Rg 2 and other protopanaxatriol (Table 1).…”
Section: Discussionsupporting
confidence: 63%
“…Ginsenosides (Rg 1 , Re or Rg 2 ) have been acknowledged as key regulators of the 5HT3A receptor during emesis. Another study reports that Rb 1 and Rg 1 exert a similar degree of inhibitory activity on the 5HT3A receptor in Xenopus laevis oocytes Min et al, 2003). The HPLC analysis of RG in this study revealed relatively high and moderate concentrations of the protopanaxadiol ginsenosides Rb 1 , Rg 3, Rc, Rb 2 , Rg 2 and other protopanaxatriol (Table 1).…”
Section: Discussionsupporting
confidence: 63%
“…1), and thus Rg1 and Rb1 would be thought of as active compounds in our experimental model. However, our previous study indicated that nonginsenoside fractions of P. ginseng also exerted protective effects, comparable with the ginsenoside fraction, on cisplatin-induced gastric damage in a rat model [51], and others also showed similar effects using nonsaponin fractions [52]. Moreover, the general formula of P. ginseng traditionally comprises the whole fraction, as the PGE used in our current study.…”
Section: Discussionsupporting
confidence: 49%
“…Kim et al showed that Ginseng extracts reduce cisplatin-induced nausea in ferrets (Kim et al, 2005 ). Steroid glycosides, called ginsenosides, are accountable for the observed 5-HT 3A receptor antagonism (Min et al, 2003 ; Lee et al, 2007 ), and their binding site in the pore region of 5-HT 3A receptors has been identified (Lee et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%